ANALISA PEMILIHAN BAHAN PADA PEMODELAN SPROKET - Feddy Wanditya Setiawan; Danang Yugo Pratomo (JMIO, 2019)
Sprocket is a chain drive component as a power transfer, starting from one shaft to another. For effective power transfer, chain sprocket is made and planned precisely. A Sprocket varies from the number of gears, measurements and types of material, for example on bicycles, motorcycles, cars, chain-wheeled vehicles, and other machines. This study uses the basis of sprocket modeling with re-engineering of the model. Testing with finite element analysis will know the strength and toughness of the sprocket to the optimum limit. Sprocket modeling is designed and simulated before operational testing. A number of materials are used, such as alloy steel, gray cast iron, carbon fiber and then a comparison of tensile stress values, total deformation, pressure and stress levels are used. The progress of this modeling process is to check the sprocket by selecting the best material. With finite element analysis based software, dimension comparisons, model designs and ideal materials are made for the sprocket. Keywords: Software FEA, manufacturing model, sprocket chain, material properties, testing simulation